Hungary as receiving country for circulars - Illés, Sándor; Kincses, Áron (Hungarian Geographical Bulletin, 2012)
The paper presents findings of research on long-term international circular migration. There is scarce information on migratory phenomena interlinked by serial numbers (parity) in literature, so we would like to provide empirical evidences on international circular migrants based on the registered-type of data. The paper draws on a conceptual framework for a sort of definition of international circular migration. We deal with the phenomenon of circulation as one of the systems of the international migration and concentrate on Hungary as a receiving country. The main aim of the paper is to transform the notion of circulation highly theorised to the practice. The paper seeks to gain further insight into the demographic composition and territorial preferences of international circular immigrants in Hungary. Conclusions about circulars indicate the need for future investigations.